2021
DOI: 10.1016/j.ymgmr.2021.100827
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of atypical myopathy based on organic acid and acylcarnitine profiles and evolution of biomarkers in surviving horses

Abstract: Background Atypical myopathy (AM), an acquired multiple acyl-CoA dehydrogenase deficiency (MADD) in horses, induce changes in mitochondrial metabolism. Only few veterinary laboratories offer diagnostic testing for this disease. Inborn and acquired MADD exist in humans, therefore determination of organic acids (OA) in urine and acylcarnitines (AC) in blood by assays available in medical laboratories can serve as AM diagnostics. The evolution of OA and AC profiles in surviving horses is unreported. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the study of Votion et al ( 2014 ) mild increases of C4, C5, C6 and C8 above the reference range were present in the horse with the lowest MCPA-carnitine concentration. The occurrence of acylcarnitines in the time profile was recently described in the study of Mathis et al (Mathis et al 2021 ), who focused on the levels of these metabolites in two horses with AM. In one of them, an increased C8 was detected by the 4th day after diagnosis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the study of Votion et al ( 2014 ) mild increases of C4, C5, C6 and C8 above the reference range were present in the horse with the lowest MCPA-carnitine concentration. The occurrence of acylcarnitines in the time profile was recently described in the study of Mathis et al (Mathis et al 2021 ), who focused on the levels of these metabolites in two horses with AM. In one of them, an increased C8 was detected by the 4th day after diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…The profile of acylcarnitines ( Figure 2A and B ) was measured over 15 days after the first signs of HGA/MCPrG poisoning. In most studies describing hypoglycin A intoxication, an increase in short (C2–C5), medium (C6–C13) and long-chain (C14–C20) acylcarnitines was observed in affected horses (Westermann et al 2008; Valberg et al 2013 ; Votion et al 2014 ; Karlíková et al 2016 ; Sander et al 2016 , 2018 ; Mathis et al 2021 ). However, in 2013 Valberg et al observed elevated C5-C10 and a slight increase of C12 and C16 in one surviving AM patient (Valberg et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the biological significance of the proteomics data set, we extensively examined if previously reported findings in blood analyses of diseased horses were also present in the proteomic analysis. Starting with CK (muscle type), we found a 22-fold elevation in AM horses compared to cograzers.…”
Section: Resultsmentioning
confidence: 99%